2017
DOI: 10.1007/s10551-017-3659-3
|View full text |Cite
|
Sign up to set email alerts
|

A Falling of the Veils: Turning Points and Momentous Turning Points in Leadership and the Creation of CSR

Abstract: This article uses the life stories approach to leadership and leadership development. Using exploratory, qualitative data from a Forbes Global 2000 and FTSE 100 company, we discuss the role of the turning point (TP) as an important antecedent of leadership in corporate social responsibility. We argue that TPs are causally efficacious, linking them to the development of life narratives concerned with an evolving sense of personal identity. Using both a multi-disciplinary perspective and a multi-level focus on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…Research has found that in some cases, major events can reconstruct one’s values, and even sublimate them ( Hemingway and Starkey, 2018 ). Once the moral characteristics are strongly triggered, they will become the stable character characteristics of the triggered person ( Hemingway and Starkey, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that in some cases, major events can reconstruct one’s values, and even sublimate them ( Hemingway and Starkey, 2018 ). Once the moral characteristics are strongly triggered, they will become the stable character characteristics of the triggered person ( Hemingway and Starkey, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing studies on the entrepreneurial motivation of commercial entrepreneurs are divided. Research found that in some cases major events restructure a person’s values and even sublimate values ( Hemingway and Starkey, 2018 ). In the life course of entrepreneurs, is there an event that changes the motivation of entrepreneurship?…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, spirituality and the religious roots of business ethics were the subjects of two articles published in Volume 1 of Research in Ethical Issues in Organizations (Duska, 1999;Primeaux & Mullen 1999). Religion and the family are two important sources of personal values that can be activated in times of crisis to motivate the way forward (Hemingway & Starkey, 2017), but my point relates to the debate about regulation that is a factor in the raised consciousness of SR.…”
Section: Activism and Regulationmentioning
confidence: 99%
“…Indeed, exemplary experiences, or turning points, were found to be factors underpinning responsible leadership within an MNC. The micro perspective on SR is particularly under-researched and there is much scope for understanding such psychological processes in SR and organizational misdemeanour (Hemingway & Starkey, 2017).…”
Section: Realising Ambition Through Inter-disciplinaritymentioning
confidence: 99%
“…etc. resulting from sustainable engagement (2016), Brockhaus et al (2017), Caldera et al (2018), Carroll (1979), C. H. Chang (2018), Dahlmann et al (2008), Delmas and Toffel (2004), Dobes et al (2017), Dooley (2017), Durdyev et al (2018), Formentini and Taticchi (2016), Ghahramani (2016), Hafenbrädl and Waeger (2017), Hemingway and Maclagan (2004), Hemingway and Starkey (2018), Henriques and Catarino (2016), Husted (2000), Jabbour and de Sousa Jabbour 2016 Variable constructs of ethical behavior, corporate citizenship, or citizenship behavior for the environment Afsar et al (2018), Baker et al (2006), Boiral et al (2018), Chen et al (2016), R. W. Cooper et al (2000), De Roeck and Farooq (2018), Desai and Kouchaki (2017), Graves and Sarkis (2018), Lin et al (2018), Ma'ayan and Carmeli (2016), Maignan et al (1999), Mo and Shi (2017), Newman et al (2017), Peake et al (2017), Razzaque and Hwee (2002), , Tosti-Kharas et al 2017, Waldman et al (2017), Y.-D. Wang and Sung (2016), Y. , Way et al (2018) 5.1%…”
Section: Vii4 Concluding Remarksmentioning
confidence: 99%